Standard Operating Procedures for Biospecimen Collection, Processing, and Storage: From the Type 1 Diabetes in Acute Pancreatitis Consortium. Issue 6 (July 2022) - Wasserfall, Clive; Dyer, Anne-Marie; Speake, Cate; Andersen, Dana K.; Baab, Kendall Thomas; Bellin, Melena D.; Broach, James R.; Campbell-Thompson, Martha; Chinchilli, Vernon M.; Lee, Peter J.; Park, Walter G.; Pratley, Richard E.; et al.
Abstract: Differences in methods for biospecimen collection, processing, and storage can yield considerable variability and error. Therefore, best practices for standard operating procedures are critical for successful discovery, development, and validation of disease biomarkers. Here, we describe standard operating procedures developed for biospecimen collection during the DREAM (Diabetes RElated to Acute pancreatitis and its Mechanisms) Study within the Type 1 Diabetes in Acute Pancreatitis Consortium. Notably, these protocols were developed using an integrative process based on prior consortium experience and with input from working groups with expertise in immunology, pancreatitis, and diabetes. Publication and adoption consistent biospecimen protocols will inform future studies and allow for better comparisons across different metabolic research efforts.